2016
DOI: 10.1038/srep33101
|View full text |Cite
|
Sign up to set email alerts
|

The fitness burden imposed by synthesising quorum sensing signals

Abstract: It is now well established that bacterial populations utilize cell-to-cell signaling (quorum-sensing, QS) to control the production of public goods and other co-operative behaviours. Evolutionary theory predicts that both the cost of signal production and the response to signals should incur fitness costs for producing cells. Although costs imposed by the downstream consequences of QS have been shown, the cost of QS signal molecule (QSSM) production and its impact on fitness has not been examined. We measured … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 63 publications
2
31
0
Order By: Relevance
“…However, when 10 µM exogenous 3O-C 12 -HSL was supplied, lasI mutants surpassed the wild type in growth (positive correlation between relative fitness and percent adenosine: coefficient, 8.74, P = 0.003) ( Fig. 2a and c ) This result is consistent with previous work demonstrating a cost to 3O-C 12 production ( 18 ). As predicted, this ability of lasI mutants to use exogenous signal, combined with the cost of signal production to the wild type, means that lasI mutants grown in coculture with wild-type bacteria act as social cheats: the average relative fitness was consistently >1 and did not decline as percent adenosine increased (coefficient, 1.8; P = 0.88) ( Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, when 10 µM exogenous 3O-C 12 -HSL was supplied, lasI mutants surpassed the wild type in growth (positive correlation between relative fitness and percent adenosine: coefficient, 8.74, P = 0.003) ( Fig. 2a and c ) This result is consistent with previous work demonstrating a cost to 3O-C 12 production ( 18 ). As predicted, this ability of lasI mutants to use exogenous signal, combined with the cost of signal production to the wild type, means that lasI mutants grown in coculture with wild-type bacteria act as social cheats: the average relative fitness was consistently >1 and did not decline as percent adenosine increased (coefficient, 1.8; P = 0.88) ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…However, little attention has been paid to whether QS signals themselves can act as exploitable public goods, despite there being a metabolic cost associated with the production of QS signals (even in the absence of downstream responses [ 18 , 19 ]). Previous experiments have shown that signal-negative mutants can act as cheats, but these were conducted under conditions where QS-dependent exoproducts enhance growth: these studies therefore do not separate the fitness effects of producing from those of responding to signal ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The variable peptide and isoprene moiety of ComX signaling molecule 19 enables this molecule to be intra-species specific 18 , 33 . High specificity has its price—our estimation of ComX molecule cost is 484 ATP, considerably more than 8 ATP for acyl-homoserine lactones (AHL) 29 based communication systems.…”
Section: Discussionmentioning
confidence: 99%
“…It was theoretically estimated that among SM, peptide signals of Gram-positive bacteria are more than 20 times metabolically more expensive than AHLs produced by Gram-negative bacteria 29 . The existence of fitness cost of signal molecule production in Gram-negative bacterial models has been theoretically predicted 30 32 and experimentally supported 33 . One would thus expect that the fitness burden of metabolically costly SM production in Gram-positives is even more pronounced.…”
Section: Introductionmentioning
confidence: 95%
“…The four genotypes each release their own QS signal at equal concentrations (Table S2). Cells bind these secreted signals in a concentration dependent manner, at which point they are induced to produce bacteriocins that kill susceptible neighbor cells at the cost of reduced growth for the producer (Ruparell et al , 2016). While two faithful-signaling genotypes are only able to respond to their own signals, the two other eavesdropping genotypes can respond to multiple signals.…”
Section: Resultsmentioning
confidence: 99%